Analisis Dampak Kegiatan Pasar Numerasi terhadap Peningkatan Hasil Belajar Siswa Kelas V UPTD Satdik SDN Curahtakir 4 - Ahmad Maulana Akbar; Septi Triyani (Lembaga Pengembangan Kinerja Dosen, 2024)
Numeracy markets are activities that imitate market situations that are closely related to everyday life. Students are given the opportunity to design, manufacture, market, and sell goods. This research aims to help students improve their numeracy skills, increase their understanding of basic mathematical concepts, and improve their social skills and creativity through numeracy market activities. This type of research is descriptive with a qualitative approach. The research subjects consisted of fifth grade students at UPTD satdik SDN Curahtakir 4. The stages in this research included observing placement schools and their problems, designing activities as solutions to problem solving, carrying out AKM pretests, carrying out numeracy market activities, carrying out AKM posttests, and then analyzing and evaluating . The research results show that it is very suitable for elementary school (SD) students because it offers new experiences in interpreting mathematical concepts. This numeracy market activity also has a positive impact on improving student learning outcomes in the context of mathematics. Apart from that, the findings from this research are that the AKM numeracy post-test scores for class V students have increased compared to the previous AKM numeracy pre-test scores.